Konstituen Makna Denotatif dan Konotatif dalam Alternative Universe ‘Throw.back’ Karya @Matchacioya di Media Sosial X - Alimah Fadhilah Can; Made Sri Satyawati; Anak Agung Putu Putra (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to identify and analyze the denotative and connotative meanings in an alternative universe (AU) entitled Throw.back by @Matchacioya uploaded on social media X. The approach used in this study is descriptive qualitative with semantic theory as the basis of analysis. Semantic theory is used to explore how the meaning of a word or phrase is formed both literally (denotative) and in a social and emotional context (connotative). The research data was obtained through the free-spirited conversational listening method, which allows researchers to understand and identify the words or phrases used in the AU. After the data was collected, the analysis was carried out using the distribution method, with the direct element division technique and the lesap technique. The direct element division technique is used to dissect the literal meaning of the word or phrase, while the lesap technique is used to understand the hidden meaning, namely the meaning formed due to the influence of the context and the emotional experiences of the characters in the AU. The results of the study show that the denotative meaning reflects the literal meaning of the word or phrase, such as the word